Voices from Srebrenica : survivor narratives of the Bosnian Genocide - Petrila, Ann, 1956-; Hasanović, Hasan, 1975-; Suljagić, Emir (Jefferson, N.C. : McFarland Publishers, 2021)
"In the hills of Eastern Bosnia sits the small town of Srebrenica--once known for silver mines and health spas, now infamous for the genocide that occurred there during the Bosnian War. In July 1995, when the town fell to Serbian forces, 12,000 Muslim men and boys fled through the woods, seeking safe territory. Hunted for six days, more than 8,000 were captured, killed at execution sites and later buried in mass graves. With harrowing personal narratives by survivors, this book provides eyewitness accounts of the Bosnian genocide, revealing stories of individual trauma, loss and resilience."--
Includes bibliographical references and index.
Keywords: Yugoslav War, 1991-1995 -- Atrocities -- Bosnia and Herzegovina -- Srebrenica; Yugoslav War, 1991-1995 -- Personal narratives, Bosnian; Genocide survivors -- Bosnia and Herzegovina -- Srebrenica; Genocide -- Bosnia and Herzegovina -- Srebrenica; Muslims -- Persecutions -- Bosnia and Herzegovina -- Srebrenica; Srebrenica (Bosnia and Herzegovina) -- History -- 20th century